2008
DOI: 10.1002/gps.2126
|View full text |Cite
|
Sign up to set email alerts
|

Helping carers to care—The 10/66 dementia research group's randomized control trial of a caregiver intervention in Russia

Abstract: The low-level intervention seems to be as, if not more, effective than similar interventions applied in high income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
145
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(156 citation statements)
references
References 23 publications
1
145
0
10
Order By: Relevance
“…This process is described in Figure 2. The selected studies were: Carrasco et al 2009 (17) , Fortinsky et al 2009 (18) , Gavrilova et al 2009 (19) , Guerra et al 2009 (20) , Hérbert et al1994 (21) , Hérbert et al 2003 (22) and Rotrou et al 2011 (23) , as described in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is described in Figure 2. The selected studies were: Carrasco et al 2009 (17) , Fortinsky et al 2009 (18) , Gavrilova et al 2009 (19) , Guerra et al 2009 (20) , Hérbert et al1994 (21) , Hérbert et al 2003 (22) and Rotrou et al 2011 (23) , as described in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies of Guerra (20) and Hérbert (22) , less than 20% of both groups were male caregivers. In the studies Gavrilova (19) and Rotrou (23) meanwhile, just over 30% of the caregivers were male.…”
Section: * Ig -Intervention Group and Cg -Control Groupmentioning
confidence: 95%
“…In accordance, Gavrilova and colleagues, who also implemented a high quality multicomponent intervention containing education and training, pointed out a decrease in caregiver burden, but could not decrease distress or improve quality of life. For recipients, no differences were found in quality of life, nor in behavioral and psychological symptoms [23]. Ducharme et al concluded that after receiving their intervention of medium methodological quality, also containing education and training, caregivers were more confident in dealing with caregiving situations.…”
Section: Individual Based Multicomponent Interventionsmentioning
confidence: 99%
“…It refers to a balance between the social, physical, and psychological resources caregivers need in order to meet their social, psychological, and physical challenges [18][19][20][21]. Although many interventions demonstrated positive impacts on different outcomes such as burden [22,23], quality of life of the caregiver [24], and delay in hospitalization [25]; other similar studies did not find the same benefits [26][27][28]. Inconsistency of the current findings can be explained by the methodological issues caused by the complex nature of this type of research, e.g., [4,[29][30][31][32][33][34][35], such as: different duration of interventions, different intensity and characteristics of interventions, and the variety of caregivers and care-recipients characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that home-based support for caregivers of persons with dementia, which emphasizes the use of locally available, low-cost human resources, is feasible, acceptable and leads to significant improvements in caregiver mental health and burden of caring. Researchers from the 10 / 66 Dementia Research Group have since tested the effectiveness of this intervention in randomized controlled trials in Peru and Russia (201,236,238). The results again indicated much larger treatment effects on caregiver psychological morbidity and strain than are typically seen in trials of such interventions in high-income countries.…”
Section: Interventions Brief Description Key Citationsmentioning
confidence: 99%